CONTINUOUS STRUGGLE OF GEORGIA WITH OCCUPATION - Bregvadze, Mariam (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is explores for independence Georgia’s varied struggle against occupation both past and present. Research methods: the chosen topic of scientific research requires the use of various scientific methods and approaches to obtain high-quality results. Therefore, the following research methods were used to solve the tasks set: analysis; systematic method; analytical method, etc. Results: along with the restoration of Georgia’s independence, the country has been fighting an ongoing battle against occupation, confronting multiple threats to its sovereignty and territorial integrity. This article explores Georgia’s varied struggle, both past and present. Significantly, despite concerted efforts to settle the situation, the occupation persists, casting a pall over the country’s hopes for peace and stability. The fundamental goal of Georgian strategy was to improve the existing procedures against the occupation. Georgia has worked to improve its defenses and obtain global support for its cause through diplomatic relations and multilateral collaborations. However, the persistent character of the occupation necessitated a thorough reconsideration of peacekeeping procedures and strategies, as evidenced by the current situation in Ukraine. Georgia hopes to improve its ability to detect and deter acts of aggression by increasing interaction with regional and international players. Furthermore, policies that foster discussion and reconciliation are critical components of any long-term peace deal. Discussion: the article seeks to depict Georgia’s ongoing struggle with occupation using dogmatic and comparative legal analysis. This approach demonstrates the critical necessity for ongoing international engagement and support. Georgia is attempting to overcome the problems of the occupation and achieve its vision of a safe future by upgrading current processes and contributing to the modernization of the peacekeeping system.